2009
DOI: 10.1158/1535-7163.mct-08-0219
|View full text |Cite
|
Sign up to set email alerts
|

Thymidylate synthase gene variations: predictive and prognostic markers

Abstract: Since its introduction more than 50 years ago by Heidelberger et al., the fluoropyrimidine 5-fluorouracil (5-FU) has remained the mainstay of therapeutic regimens used in the treatment of colorectal cancer and other human malignancies, with single-agent response rates of 20% to 25% in advanced disease stage. Pharmacogenomics has emerged as a useful tool to address interindividual gene variations by analyzing the interplay of host and tumor genotype and drug efficacy and toxicity. Having a reliable panel of pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
48
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(54 citation statements)
references
References 35 publications
5
48
0
1
Order By: Relevance
“…Although high TS has predicted poor response to therapy in a range of tumors (Pestalozzi et al 1997, Huang et al 2000, Harpole et al 2001, Mizutani et al 2001, Lurje et al 2009, little is known of its possible role as a therapeutic marker in GEPs. Recently, in Endocrine-Related Cancer (2010) 17 847-856…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although high TS has predicted poor response to therapy in a range of tumors (Pestalozzi et al 1997, Huang et al 2000, Harpole et al 2001, Mizutani et al 2001, Lurje et al 2009, little is known of its possible role as a therapeutic marker in GEPs. Recently, in Endocrine-Related Cancer (2010) 17 847-856…”
Section: Discussionmentioning
confidence: 99%
“…High thymidylate synthase (TS) protein and mRNA expression have been associated with poor clinical outcome in patients treated with 5-fluorouracil (5-FU)-based protocols in esophageal (Harpole et al 2001), breast (Pestalozzi et al 1997), bladder (Mizutani et al 2001), and non-small cell lung cancers (Huang et al 2000). The same has been applied to CRC, although with conflicting results (Lurje et al 2009). Similarly, the protein kinase Akt, an important player in phosphatidylinositol-3 kinase activation (cell proliferation, growth, and survival), has been identified as a possible maker of response and survival in some tumors.…”
Section: Introductionmentioning
confidence: 99%
“…The authors showed that tumors expressing high levels of TS seemed to have poor overall survival (OS) compared with tumors expressing low TS levels (Popat et al, 2004). TS gene expression is modulated by functional, significant germ-line polymorphisms in the 5¢-UTR thymidylate synthase enhancer region (TSER), and 3¢-UTR (TS 1494del6b) of the gene (Horie et al, 1995;Mandola et al, 2003;Lurje et al, 2009). A variable number of tandem repeats (VNTR) in the promoter region of TS (TSER), mainly 2 (2R) and 3 repeats (3R), and cytosine versus guanine single-nucleotide polymorphism (SNP) can influence the efficiency of translation (Mandola et al, 2003;Lurje et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…5-FU is also incorporated into RNA, and RNA-based effects play a significant role in its cytotoxicity (11). The sensitivity of cancer cells to 5-FU is often influenced by the expression levels of the target enzyme TS and the metabolic enzymes for 5-FU, including thymidine phosphorylase (TP), dihydropyrimidine dehydrogenase (DPD), orotate phosphoribosyl transferase (OPRT), uridine phosphorylase (UP), uridine kinase (UK) and thymidine kinase (TK) (12)(13)(14). The expression of selected elements of the 5-FU metabolic pathway ( Fig.…”
Section: Introductionmentioning
confidence: 99%